Factibilidad financiera de la mejora de las redes generales de distribución de la unidad de negocio centro occidente de la Comisión Federal de Electricidad - Tinoco Martínez, Maria del Rayo (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
Under the rules defined by the legal framework of the Energy Reform instructed by the Federal Government, establishes the role, objectives and goals of each area of the CFE independently. It is necessary to take the organization to a new level of performance, to reaffirm itself as a committed energy company with its clients, with attractive profitability and financial stability. It is necessary to take the organization to a new level of performance, to reaffirm itself as a committed energy company with its clients, with attractive profitability and financial stability. The present study shows the Investment Project of the Western Central Business Unit of the Federal Electricity Commission, which underpins its ability to finance, maximizes flow generation, optimizes capital investment and achieves a competitive cost structure. This investment plan is prepared over a five-year horizon, with a maximum capital allocation, which translates into a limit for each business area and is reflected in the guidelines and return required by the Energy Secretariat for the approval of investments. Through the prioritization of core businesses, evaluated through the application of profitability criteria and the useful life of the inputs, the technical and financial profitability of the Business Unit Centro Occidente is demonstrated; with an adequate selection of the investments, through the prospect of the electric market, with a logic of social value, towards the fulfillment of its mandate of generating value, oriented to transform the Electrical Distribution System into an Intelligent Network, with a deep analysis of the performance of operational indicators and the needs of the General Distribution Networks.

Bajo las reglas definidas por el marco legal de la Reforma Energética instruida por el Gobierno Federal, establece el rol, los objetivos y las metas de cada una de las áreas de la CFE de manera independiente. Es necesario llevar a la organización a un nuevo nivel de desempeño, reafirmarse como una empresa de energía comprometida con sus clientes, con rentabilidad atractiva y estabilidad financiera. El presente estudio muestra el Proyecto de Inversión de la Unidad de Negocio Centro Occidente de la Comisión Federal de Electricidad, con el cual apuntala su capacidad de financiarse, maximiza la generación de flujo, optimiza la inversión de capital y logra una estructura de costos competitiva. Este plan de inversiones está elaborado a un horizonte de 5 años, con una asignación máxima de capital, que se traduce en un límite para cada área de negocio y se refleja en los lineamientos y el retorno exigidos por la Secretaría de Energía para la aprobación de inversiones. A través de la priorización de negocios medulares, evaluados mediante la aplicación de criterios de rentabilidad y el periodo de vida útil de los insumos, se demuestra la rentabilidad técnica y financiera de la Unidad de Negocios Centro Occidente; con una adecuada selección de las inversiones, mediante la prospectiva del mercado eléctrico, con una lógica de valor social, hacia el cumplimiento de su mandato de generación de valor, orientadas a transformar el Sistema Eléctrico de Distribución en una Red Inteligente, con un análisis profundo del desempeño de los indicadores operativos y las necesidades de las Redes Generales de Distribución.
Facultad de Contaduría y Ciencias Administrativas. Maestría en Administración
Keywords: info:eu-repo/classification/cti/5; FCCA-M-2018-0689; Reforma energética; Rentabilidad; Negocios medulares; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6151